Dicer in Macrophages Prevents Atherosclerosis by Promoting Mitochondrial Oxidative Metabolism. Issue 18 (30th October 2018) - Wei, Yuanyuan; Corbalán-Campos, Judit; Gurung, Rashmi; Natarelli, Lucia; Zhu, Mengyu; Exner, Nicole; Erhard, Florian; Greulich, Franziska; Geißler, Claudia; Uhlenhaut, N. Henriette; Zimmer, Ralf; Schober, Andreas
Abstract : Background: Alternative macrophage activation, which relies on mitochondrial oxidative metabolism, plays a central role in the resolution of inflammation and prevents atherosclerosis. Moreover, macrophages handle large amounts of cholesterol and triglycerides derived from the engulfed modified lipoproteins during atherosclerosis. Although several microRNAs regulate macrophage polarization, the role of the microRNA-generating enzyme Dicer in macrophage activation during atherosclerosis is unknown. Methods: To evaluate the role of Dicer in atherosclerosis, Apoe −/− mice with or without macrophage-specific Dicer deletion were fed a high-fat diet for 12 weeks. Anti-argonaute 2 RNA immunoprecipitation chip and RNA deep sequencing combined with microRNA functional screening were performed in the Dicer wild-type and knockout bone marrow–derived macrophages to identify the individual microRNAs and the mRNA targets mediating the phenotypic effects of Dicer. The role of the identified individual microRNA and its target in atherosclerosis was determined by tail vein injection of the target site blockers in atherosclerotic Apoe −/− mice. Results: We show that Dicer deletion in macrophages accelerated atherosclerosis in mice, along with enhanced inflammatory response and increased lipid accumulation in lesional macrophages. In vitro, alternative activation was limited whereas lipid-filled foam cell formation was exacerbated in Dicer -deficient macrophages as a result of impaired mitochondrial fatty acid oxidative metabolism. Rescue of microRNA (miR)-10a, let-7b, and miR-195a expression restored the oxidative metabolism in alternatively activated Dicer -deficient macrophages. Suppression of ligand-dependent nuclear receptor corepressor by miR-10a promoted fatty acid oxidation, which mediated the lipolytic and anti-inflammatory effect of Dicer. miR-10a expression was negatively correlated to the progression of atherosclerosis in humans. Blocking the interaction between ligand-dependent nuclear receptor corepressor and miR-10a by target site blockers aggravated atherosclerosis development in mice. Conclusions: Dicer plays an atheroprotective role by coordinately regulating the inflammatory response and lipid metabolism in macrophages through enhancing fatty acid–fueled mitochondrial respiration, suggesting that promoting Dicer/miR-10a–dependent metabolic reprogramming in macrophages has potential therapeutic implications to prevent atherosclerosis. Abstract : Supplemental Digital Content is available in the text.